Design and performance of shattered pellet injection systems for JET and KSTAR disruption mitigation research in support of ITER. (25th August 2021) - Baylor, L.R.; Meitner, S.J.; Gebhart, T.E.; Caughman, J.B.O.; Shiraki, D.; Wilson, J.R.; Craven, D.; Fortune, M.; Silburn, S.; Muir, A.; Peacock, A.T.; Park, S.H.; et al.
Abstract: Shattered pellet injection (SPI) systems that form cryogenic pellets in a pipe-gun for injection of material to mitigate disruptions have been fabricated and installed for use in thermal mitigation and runaway electron (RE) dissipation experiments on JET and KSTAR. These systems are to support disruption mitigation research for ITER and are based on an ORNL three-barrel design for flexibility in pellet size selection and variable pellet composition studies. The SPI systems for JET and KSTAR have a common feature of the barrels being collimated into a single injection line that enters the vacuum vessel. The pellets are shattered in bent stainless steel tubes that are mounted inside the vacuum vessel of the tokamak, vertically on JET and horizontally on KSTAR. The JET installation has the unique feature of vertical SPI mounting and injection with the shatter plume aimed toward the inner wall to intercept known RE beam locations generated from argon gas injection induced disruptions. The KSTAR SPI installation has two identical SPIs that are mounted on the midplane 180 degrees apart with identical injection lines and shatter tubes aimed at the plasma magnetic axis. Installation and operation of these SPI systems has provided useful lessons learned in the implementation of this SPI technology and valuable experience in optimizing the formation and firing of the pellets to optimize the physics performance.